Peran Kepemimpinan Kepala Sekolah Sman 10 Batang Hari Dalam Pengelolaan Kurikulum Merdeka - Raganata, Raganata; Ilham, Muhammad; Sukatin, Sukatin; Arfi, Ridho Ramadhan (Journal of Islamic Education, 2025)
This study aims to describe and analyze the leadership role of the principal of SMAN 10 Batang Hari in managing the Independent Curriculum, as well as the supporting factors and obstacles encountered throughout its implementation. The study used a qualitative approach with a case study design at the SMAN 10 Batang Hari educational unit. Data were collected through in-depth interviews with the principal, several subject teachers, the school committee, and observation of documentation related to the planning, implementation, and evaluation of the Independent Curriculum. Initial findings indicate that the principal's primary role includes strategic planning for the implementation of the Independent Curriculum, strengthening teacher capacity through ongoing professional development, and enhancing collaboration among various stakeholders. A transformational leadership style is considered important in building a shared vision, increasing staff commitment, and encouraging learning innovation. However, obstacles such as limited resources, resistance to curriculum change, and administrative challenges are also identified. Practical implications for school policymakers and suggestions for further research are presented to strengthen the successful implementation of the Independent Curriculum at the senior high school level.